(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2009)
The purpose of this research work was to prepare a gastroretentive drug delivery system of Famotidine. This study investigated utility of a 3-factor, 3-level Box-Behnken design and optimization process for floating tablet of famotidine with 5 replicates of center points. Amount of HPMC K4 (Hydroxy Propyl Methyl cellulose), amount of NaHCO3 and amount of citric acid were selected as the independent variables whereas total floating time (TFT), half life, % cumulative drug release at 10 hrs, and diffusion coefficients (n) were selected as dependent variables. The prepared tablets of famotidine were evaluated for dissolution study and found to follow zero order release kinetic. The responses were analyzed using ANOVA and the individual response parameters were evaluated using F test and polynomial equation was generated for each response using MLRA. The amount of HPMC K4 and amount of citric acid were found to significantly influence all response parameters selected whereas the amount of NaHCO3 has significant effect on TFT. Optimum amount of HPMC K4, NaHCO3, and citric acid is important in achieving good floating time and minimum floating lag time. It was clear from dissolution profiles that the tablets of batch F3, F7, and F12 exhibits initial burst phase during the first hour of dissolution. The burst phase was followed by a limited drug release for the rest of the period. The produced tablets exhibited good floating time and controlled drug release over a period of 12 h. The resultant data were critically analyzed to locate the composition of optimum formulations. All predicted values of response variables of optimized formulation demonstrated close agreement with the experimental data during optimization procedure.